Measuring Mobility Gaps: A Quantitative Study of Affordability, Reliability and Safety Issues in Kathmandu’s Public Transport System - Basnet, Asmita; Shrestha, Sneha; Limbu, Suraj Kurungwang; Shrestha, Shraddha; Tamang, Badri (NPRC Journal of Multidisciplinary Research, 2025)
Background: Public transport is the primary mobility source in Nepal's cities, particularly the densely populated Kathmandu Valley. Despite its importance, the system is plagued with long-standing affordability, dependability, safety, and accessibility problems with disproportionate effects on marginalized groups. Route No. 5 is one such systemic example reflective of broader national issues in public transport. Objectives: The current study aimed to (1) assess commuter attitudes towards quality of service, (2) examine socioeconomic disparities in transport access, (3) identify key service gaps, (4) suggest evidence-based policy measures, and (5) contribute to sustainable urban mobility with Nepal's development agenda. Methods: Quantitative survey of 141 Route No. 5 commuters using a structured questionnaire was conducted. Data on affordability, reliability, safety, and accessibility were obtained through face-to-face interviews and analyzed using SPSS (descriptive statistics, cross-tabulations). Cronbach's alpha (α > 0.7) was used to establish reliability. Findings: The findings were: Affordability: 63.8% thought fares were affordable, but 28.4% (mostly students and low-income groups) had financial burdens (Table 2). Reliability: 34.8% perceived services as unreliable, including peak-hour delays and overloading (Table 3). Safety: 27% felt unsafe in the evening, with women citing harassment (Table 4). Accessibility: 43.3% reported limited evening services; 72% cited inadequate disability infrastructure (Table 5) Conclusion: The study reveals urgent needs for fare subsidies, improved frequency of services, more nighttime safety measures (e.g., CCTV, women-only transport), and disability-accessible infrastructure. Policy reforms must give precedence to equitable access and enforcement of service standards. Novelty: The paper presents empirical, route-level data to fill Nepal's public transport gaps, linking micro-level commuter experience to macro-level policy solutions.